PENERAPAN MODEL TEAM ASSISSTED INDIVIDUALLY UNTUK MENINGKATKAN HASIL BELAJAR SISWA IV SDN ILOT - Nasri Diana; Rita Zahara (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2020)
This study aims to determine the improvement of student learning outcomes through the implementation of the Team Assisted Individually model. The research method used is qualitative using the PTK model. The subjects in this study were 18 of 4th grade students. Data collection was carried out through observation, tests, and documentation. Data processing was carried out by means of data tabulation and data interpretation. The results showed that the acquisition of student learning outcomes was seen from the average value in cycle I was 65 and cycle II was 82.2. Student learning completeness in cycle I was 27.7% and cycle II was 100%. Therefore, it can be concluded that the application of the Team Assisted Individually model can improve student learning outcomes.